“I Ought to Be Getting Him His Feed”: Masculinity Regained in Edith Wharton’s Ethan Frome - Yoshino Narumi (Gender Studies, 2023)
This paper discusses the masculinity of the protagonist Ethan in Edith Wharton’s Ethan Frome in relation to the vehicles he uses. Ethan, who attempts to commit suicide by sledding down a hill with his wife’s cousin Mattie so as to flee his unhappy marriage, but fails and becomes physically crippled in the end, is commonly interpreted as a symbolically demasculinized loser. Against this common (and sensible) interpretation, this essay will focus on his use of carriage, sled, and horses, as his source of mobility, and analyze them in their social and literary contexts to confirm his struggle to regain masculinity.